Keterlibatan Publik dalam Optimalisasi Aplikasi E-Samsat di Kota Padang - Eldsando Zheska, Naufal; Malau, Hasbullah (Policy, Law and Political Research Center, 2024)
This research is motivated by the hope and desire to realize optimal public services in Padang City through the e-Samsat application as a means of providing information regarding motor vehicle taxes. This research aims to assess the extent of optimal service through the e-Samsat application as well as the obstacles that influence the application optimization process. This research adopts a qualitative approach employing descriptive methods. Data gathering involves observation, interviews, and documentation. The validity of the data is assessed through source triangulation, technical triangulation, and time triangulation The data analysis involves methods such as reducing data, presenting findings, and making conclusions. The outcomes indicate that optimizing the e-Samsat application is by providing public space. The elements in this public space are monitoring, participation and accountability. Public space in efforts to optimize e- Samsat has gone quite well, however there are obstacles that have a big influence on this, namely, the quality of human resources, inadequate budget from the Padang City Samsat UPTD.